2012
DOI: 10.1308/003588412x13373405386457
|View full text |Cite
|
Sign up to set email alerts
|

Breast reconstruction with deep inferior epigastric perforator flaps

Abstract: INTRODUCTIONApproximately 45,000 women are diagnosed with breast cancer in the UK each year. The success of screening and the introduction of adjuvant therapies have meant that prognosis is improving and an increasing number of patients are seeking reconstruction following mastectomy. The purpose of this study was to evaluate the deep inferior epigastric perforator (DIEP) flap reconstructions performed in Stoke Mandeville Hospital and, through analysis of complications, detail the evolution of the current care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…This result focuses on a short critical period at the beginning of the practice and confirms the highest level of complication risk [13,14]. In a recent study, Kreymerman et al produced results that contradicted the DIEP learning curve theory [22].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This result focuses on a short critical period at the beginning of the practice and confirms the highest level of complication risk [13,14]. In a recent study, Kreymerman et al produced results that contradicted the DIEP learning curve theory [22].…”
Section: Discussionsupporting
confidence: 55%
“…They succeeded in drastically reducing their complication rate after adopting several technical changes and visiting an external team of experienced surgeons. [14]. In our study, we demonstrated a significant DIEP learning curve regarding three parameters: surgical time, surgical revision rate, and postoperative hospital stay.…”
Section: Discussionmentioning
confidence: 54%
“…The perforator vessels from the abdominal flap are anastomosed onto the internal mammary vessels that are approached by removing a small portion of rib. 6 Figure 4 illustrates how the DIEP procedure is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Such complications include not only generic surgical risks including bleeding, infection, and seromas but also procedure-specific complications such as mastectomy flap or abdominal apron necrosis or both and pulmonary injury. Partial fat necrosis in DIEP flaps has been estimated to occur in 9%-17% of patients 89,90 ; however, total flap failure rates have been generally reported to be less than 2% in high-volume centers. 91 Major complications such as pulmonary embolus or death are equally rare.…”
Section: Complicationsmentioning
confidence: 99%